Patent Landscape Report - Hydrogen fuel cells in transportation (World Intellectual Property Organization, 2022)
Over the next decade, transforming the transportation sector to put it on a Net Zero pathway will require a combination of technological innovation, government and corporate decision-making, and adapted customer behavior. Reducing greenhouse gas emissions by transportation, a sector responsible for almost 24 percent of direct carbon dioxide emissions from fuel combustion is crucial. This WIPO Patent Landscape Report provides early observations on patenting activity together with complementary information from online news, press releases and corporate financial reporting in the field of hydrogen fuel cells in transportation.